2000
DOI: 10.1016/s0022-5223(00)70136-x
|View full text |Cite
|
Sign up to set email alerts
|

Extended total arch replacement for acute type a aortic dissection: Experience with seventy patients

Abstract: Extended total arch replacement for acute type A aortic dissection could be justified in properly selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
121
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(128 citation statements)
references
References 27 publications
(40 reference statements)
3
121
0
4
Order By: Relevance
“…In an effort to maximize the resection of entry tears and to decrease the incidence of residual patent false lumina, several groups [4][5][6][7]11,12 have advocated a more aggressive approach to aortic arch repair: routine replacement of the total aortic arch regardless of the site of the entry tear, although distal manipulation has been associated with an increased operative mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to maximize the resection of entry tears and to decrease the incidence of residual patent false lumina, several groups [4][5][6][7]11,12 have advocated a more aggressive approach to aortic arch repair: routine replacement of the total aortic arch regardless of the site of the entry tear, although distal manipulation has been associated with an increased operative mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Because the residual dissection flap in the aortic arch and descending aorta carries risks of progressive aortic dilation and rupture and the need for secondary intervention, several groups have suggested immediate extensive surgery that involves the aortic arch, although concomitant distal aortic manipulation has been associated with an increased risk of morbidity and death. [4][5][6][7][8][9][10][11][12][13] In this situation, 2 different surgical strategies have been proposed: total arch replacement or hemiarch replacement (a more conservative repair limited to the ascending aorta and proximal arch). 4,[9][10][11][12] We evaluated the early and intermediate outcomes of aortic arch surgery in patients with type A AAD, investigating the effect, upon postoperative results, of aortic arch extension.…”
mentioning
confidence: 99%
“…3,[5][6][7] The main benefit of this approach is the complete resection of a small, invisible entry site located in the aortic arch. 6) We have recently reported that the patent false lumen of the distal aorta were associated with late, distal aortic enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…In 1983, Borst introduced the elephant trunk procedure [3], followed by a variety of modifications [4][5][6], with improved clinical outcomes over the years [7][8][9]. Recently, endovascular placement of stent grafts and hybrid repair have also emerged as new treatment options [10,11].…”
Section: Introductionmentioning
confidence: 99%